Dornase alfa improves the health-related quality of life among Brazilian patients with cystic fibrosis - A one-year prospective study - Rozov, Tatiana; De Oliveira, Viviane Ziebell; Santana, Maria Angélica; Adde, Fabíola Villac; Mendes, Rita Heloisa; Paschoal, Ilma Aparecida; Caldeira Reis, Francisco J.; Shinzato Higa, Laurinda Yoko; De Castro Toledo Jr., Antonio Carlos; Pahl, Márcia; De Abreu E Silva, Fernando; Gramacho, Ana Paula; et al. (Wiley, 2010)
Background: Health-related quality of life (HRQOL) measurements provide valuable information about the psychological and social impact of treatment on patients with cystic fibrosis (CF). This study evaluated the HRQOL of Brazilian patients with CF and assessed the changes in HRQOL domains over 1 year after dornase alfa (Pulmozyme) introduction. Patients and Methods: One hundred fifty-six stable patients with CF and 89 caregivers answered the Portuguese-validated version of the Cystic Fibrosis Questionnaire-Revised (CFQ-R) at baseline (T 0), and at 3 (T 1), 6 (T 2), 9 (T 3), and 12 (T 4) months of follow-up. Eighteen patientswere excluded because they did not fulfill the inclusion criteria. The patients were analyzed in two groups: those aged 6-11 years and those aged 14 years and older. ANOVA for observed repeated results and the last observation carried forward (LOCF) method for missing data were used for the statistical analysis. Results: After 1 year of follow-up, there was significant improvement in respiratory symptoms (T 4-T 0=8.1; 95% confidence interval (95% CI)=[2.1;14.0]; effect size (ES)=0.35; P<0.001), Emotional Functioning (T 4-T 0=5.6; 95% CI=[1.1;10.1]; ES=0.31; P<0.05), Social Functioning (T 4-T 0=6.0; 95% CI=[1.3;11.7]; ES=0.31; P<0.05), Body Image (T 4-T 0=11.9; 95% CI=[4.1;19.7]; ES=0.42; P<0.05), and Treatment Burden (T 4-T 0=5.3; 95% CI=[0.3;10.3]; ES=0.24; P<0.05) domains in the younger group. A significant improvement in Role Functioning (T 4-T 0=6.1; 95% CI=[1.1;11.1]; ES=0.40; P<0.05), Body Image (T 4-T 0=12.6; 95% CI=[3.5;21.7]; ES=0.46; P<0.05), and Weight (T 4-T 0=11.7; 95% CI=[1.8;21.6]; ES=0.40; P<0.05) was obtained in the older group. The caregivers' CFQ-R showed improvements in the Digestive Symptoms (T 4-T 0=5.5; 95% CI=[1.5;9.4]; ES=0.30; P<0.05), Respiratory Symptoms (T 4-T 0=7.6; 95% CI=[3.9;11.4]; ES=0.48; P<0.05), and Weight (T 4-T 0=10.1; 95% CI=[1.6;18.6]; ES=0.26; P<0.05) domains. Conclusion: The introduction of dornase alfa improved the HRQL of the patients with CF during the first year of treatment. © 2010 Wiley-Liss, Inc.
Keywords: Cystic fibrosis; Quality of life; rhDNase; Treatment; dornase alfa; adolescent; adult; aged; analysis of variance; body image; Brazil; caregiver; child; clinical trial; cystic fibrosis; digestive system disease; emotion; female; follow up; human; major clinical study; male; multicenter study; preschool child; priority journal; prospective study; quality of life; questionnaire; respiratory tract disease; school child; social aspect; statistical analysis; Adolescent; Child; Cystic Fibrosis; Deoxyribonuclease I; Expectorants; Female; Forced Expiratory Volume; Humans; Male; Prospective Studies; Quality of Life